2018
DOI: 10.1055/s-0039-1681088
|View full text |Cite|
|
Sign up to set email alerts
|

Leveraging Electronic Dental Record Data to Classify Patients Based on Their Smoking Intensity

Abstract: Background Smoking is an established risk factor for oral diseases and, therefore, dental clinicians routinely assess and record their patients' detailed smoking status. Researchers have successfully extracted smoking history from electronic health records (EHRs) using text mining methods. However, they could not retrieve patients' smoking intensity due to its limited availability in the EHR. The presence of detailed smoking information in the electronic dental record (EDR) often under a separate section allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It allows the algorithm to always converge without regard of the dimensionality (17). A recent study on dental health records from the US found that SVM performed best to classify patients according to smokers, non-smokers, and unknowns, with a PPV and sensitivity of 98% and F-score of 0.98 (8). In addition, that study included an assessment of the patient's tobacco consumption, but it was limited to three classifiers instead of four as in our study and there was no consideration of the cost matrix.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It allows the algorithm to always converge without regard of the dimensionality (17). A recent study on dental health records from the US found that SVM performed best to classify patients according to smokers, non-smokers, and unknowns, with a PPV and sensitivity of 98% and F-score of 0.98 (8). In addition, that study included an assessment of the patient's tobacco consumption, but it was limited to three classifiers instead of four as in our study and there was no consideration of the cost matrix.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the previous work addressing the methods for classifying patients' smoking status has been conducted as a result of the 'Smoking challenge' (7,21,22,(28)(29)(30)(31)(32), and by others who continued building on that work (5,6,33). A recent US study on dental health records developed a similar model based on machine learning (8). However, to our knowledge, there is no such prior work performed on Swedish data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported a deep-learning model that automated the staging and grading of periodontitis [ 26 ]. Finally, a few studies have reported methods to extract PD risk factors information, such as smoking, diabetes, and cardiovascular diseases from the EDR [ 27 , 28 , 29 , 30 ]. Yet, to the best of our knowledge, no study has utilized longitudinal EDR data to study PD change and its clinical course over time.…”
Section: Introductionmentioning
confidence: 99%
“…The increased availability of longitudinal patient care data electronically through the electronic dental record (EDR) offers an opportunity to characterize the present patient population's demographics, disease profiles to develop prediction models with up-to-date information (Song et al, 2013 ; Patel et al, 2018 ; Thyvalikakath et al, 2020 ). Moreover, advanced machine learning (ML) methods provide us with an opportunity to develop sophisticated data-driven models for PD.…”
Section: Introductionmentioning
confidence: 99%